Analisis Kandungan Fosfor Pada Pupuk Organik Cair Berbahan Dasar Limbah Daun Ubi Kayu, Buah Mangga dan Bayam Dengan Variasi Bioaktivator (EM-4 Untuk Tanaman dan Ragi Tape) - Ramli Ramli; Mikhratunnisa Mikhratunnisa (Universitas Katolik Widya Karya Malang, 2023)
Organic waste is waste consisting of biological elements that have a high level of bacterial reproduction so that it needs to be processed into materials that are useful for plants. Therefore organic waste which is a container as a place for the growth of bacteria and microorganisms, organic waste which can be used as liquid organic fertilizer. Organic fertilizers can be made by a fermentation process that uses a mixture of tape yeast starter and Em-4 as a bioactivator. The purpose of this study was to determine the differences in phosphorus content in liquid organic fertilizers made from waste (Cassava Leaves, Mango Fruit and Spinach) using EM-4 bioactivators for Plants and Tape Yeast. The method used in this research is the experimental method. The parameter to be tested in this study is the phosphorus content test. According to the Regulation of the Minister of Agriculture No.28/SNI/Permentan/OT.140/2/2009 which states that the standard for liquid organic fertilizer with a minimum pH of 6.8 is a maximum of 7.49 and phosphorus (p2o2) is a minimum of 0.10%.